A comprehensive review of musical creativity through the lens of bibliometric analysis - Yujia, Yang; V. Selvarajah, Indra; Foong, Ang Mei (Artseduca, 2024)
Objective: Scholars have recently observed a significant advancement in musical creativity (MC). This assessment represents a change in comprehending and interacting with musical ingenuity across diverse cultures and fields of study. Given these recent changes, the present study aims to conduct a bibliometric analysis to elucidate the chronological stages of MC’s expansion and investigate the influence of international collaboration on its progress. The objective is to examine the specific countries’ contribution to the sector and comprehend the dynamics of cross-border collaborations in promoting creativity. Method: The study examines the increasing focus on countries such as China, Spain, Australia, the United Kingdom, and the United States through a thorough bolometric analysis. This study evaluates the scope and characteristics of global collaboration in addition to the impact of the digital age on the innovation of music. This review study primarily examines the noticeable increase in musical creativity, driven by the efficacy of knowledge exchange and intricate problem-solving in the field of MC. Results: Moreover, the results demonstrate that the digital age has a beneficial impact on increasing the subject matter and research methods used in MC research. This report emphasises the necessity of a comprehensive, worldwide approach to researching and improving MC. The text proposes redirecting future research efforts towards utilising international collaboration and digital advances to advance the area. This technique has the potential to revolutionise the development of musical creativity, placing it at the forefront of both academic and practical exploration. © 2024, Artseduca. All rights reserved.